2017
DOI: 10.3390/md15110345
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polysaccharides from Grateloupia filicina and Their Antiviral Activity to Avian Leucosis Virus Subgroup J

Abstract: In this study, polysaccharides from Grateloupia filicinia (GFP) were extracted and several low molecular weight (Mw) G. filicina polysaccharides (LGFPs) were prepared by the hydrogen peroxide (H2O2) oxidation method. Additionally, the effect of different experimental conditions on the degradation of GFP was determined. Results showed that the GFP degradation rate was positively related to H2O2 concentration and temperature, and negatively related to pH. Chemical analysis and Fourier transform infrared spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The forward and reverse primers for ALV-J were 5′-TGCGTGCGTGGTTATTATTTC-3′ and 5′-AATGGTGAGGTCGCTGACTGT-3′, respectively; and the forward and reverse primer for internal control GAPDH were 5′-GAACATCATCCCAAGCGTCCA-3′ and 5′-CGGCAGGTCAGGTCAACAAC-3′. The real-time PCR were performed at 95°C for 30 s, 95°C for 5 s and 60°C for 34 s (34 cycles), 95°C for 15 s, and 60°C for 60 s [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The forward and reverse primers for ALV-J were 5′-TGCGTGCGTGGTTATTATTTC-3′ and 5′-AATGGTGAGGTCGCTGACTGT-3′, respectively; and the forward and reverse primer for internal control GAPDH were 5′-GAACATCATCCCAAGCGTCCA-3′ and 5′-CGGCAGGTCAGGTCAACAAC-3′. The real-time PCR were performed at 95°C for 30 s, 95°C for 5 s and 60°C for 34 s (34 cycles), 95°C for 15 s, and 60°C for 60 s [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cell membrane cannot be crossed when the molecular weights of the TPSs were large (e.g., 10.88 kDa of TPS0) [25,26]. However, the hydrogen chain was weak, and the active helical structure was not formed because of the short sugar chain [27,28] when the molecular weight of TPSs was small (such as 2.31 kDa of TPS3), thereby leading to a decrease in the protective effect. Thus, TPS2 with moderate molecular weight (4.82 kDa) was the most active.…”
Section: Reduction Of Cytotoxicity Of Com Crystals Aftermentioning
confidence: 99%
“…When the polysaccharide's MW is too small (such as TPS3), the sugar chain is short and the hydrogen bonding is weak; as such, an active helical structure cannot easily form. Thus, excessive ROS in the damaged cells cannot be effectively removed, the repair effect is poor [51], and the ability to promote endocytosis is weak. Liao et al [52] also showed that polysaccharides with moderate MW of 1 × 10 5 − 4 × 10 5 Da have the highest activity, while those with low MW (5 × 10 3 − 1 × 10 4 Da) have no biological activity.…”
Section: Effect Of Molecularmentioning
confidence: 99%